Imagens poéticas do tempo e memória em Lindolf Bell - Piccininn, Rosana Salete (2009)
This present work has like objective to built considerations about the subjects poetic imagens of the time and lyric memory of Catarinense poet Lindolf Bell. The choise by Bell s work justify the relevance of the author s work in the wider board of the literature in the state of Santa Catarina and in Brazil, well as the recognition that his work reached in abroad, in spite to continue little unknown in the university means. The referencial theoretical the subjects of poetic imagens of the time and memory, including, also, correlatives subjects, how is the case of the recurrence at the mythology, the childhood remembrances, and the relation between the poetic construction and the remembrance, subjects that also are approached in the text. It gives attention at the subject of the time and memory because this is a subject recurrent in the literature of all times. The dissertation shows composed by three chapters, being that, in the first, is exposed the social and poetic trajectory from Lindolf Bell, the movements that himself leaded, well as at the other movements in vogue in the period. In the second chapter, observes the lyric and social memory in the poetic of Lindolf Bell and the paper of the poetry in our society. In the third chapter, is analyzed the imaginary and the memory, searching to demonstrate the influence of memory in the poetic doing of Bell, having the myths present in the poems and by the images and symbols used in the poetic building, pointing out that the reconquest of the ancient myths present as a form of last remembrance. It is aimed, still, to observe how the memory theme, in the Bell s lyric, it finds joined at the symbol representation, in other words, the influence that the memory exercises over the images and symbols, which the poet uses. The present bibliographical research is basis in the imaginary Theory, in the Critic and in the Phenomenology, sheltering in the theoretical perspective of authors like Mircea Eliade, Gaston Bachelard, Gilbert Durand, Octavio Paz, Maurice Halbwachs, Eclea Bosi and Alfredo Bosi, Bergson, Halbwachs, Pollak, Paul Ricoeur, and others.